Pengaruh Pendampingan Orangtua Terhadap Kemandirian dan Tanggung Jawab Anak Selama Belajar dari Rumah - Ratna Pangastuti; Fifi Pratiwi; Kammariyati Kammariyati; Alma’atus Fahyuni (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
The problem in this study is how the influence of parental assistance on children's independence and responsibility while learning from home is seen from parental assistance at RA Al-Amien Kamal Bangkalan. This study aims to describe the effect of parental assistance on children's independence and responsibility while learning from home. Our research is using quantitative research. The population of this research is the parents of B3 grade children at RA Al - Amien. Learning in kindergarten or RA schools in this study uses online learning with the guidance of parents and teachers at school. Students do online learning and interact with teachers using the Whatsapp Group application. This study aims to determine the effect of parental assistance on children's independence and responsibility while learning from home. Respondents taken were parents of students in the Perumnas Kamal Bangkalan area. The results showed that parental assistance greatly influences the independence and responsibility of children while learning from home.